2020
DOI: 10.3390/ijms21124458
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Enamel and Its Dynamic Protein Matrix

Abstract: Tooth enamel is the outer covering of tooth crowns, the hardest material in the mammalian body, yet fracture resistant. The extremely high content of 95 wt% calcium phosphate in healthy adult teeth is achieved through mineralization of a proteinaceous matrix that changes in abundance and composition. Enamel-specific proteins and proteases are known to be critical for proper enamel formation. Recent proteomics analyses revealed many other proteins with their roles in enamel formation yet to be unraveled. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 144 publications
(250 reference statements)
2
54
0
4
Order By: Relevance
“…Intermolecular interactions at the nanometer level and interactions of nano-and microcrystalline structures strongly determine the properties of each material, also biological ones. The bone and the dental structures are special examples of nano-and micro-composite materials, of which the constituent particles and macromolecular structures are both of organic and inorganic nature [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular interactions at the nanometer level and interactions of nano-and microcrystalline structures strongly determine the properties of each material, also biological ones. The bone and the dental structures are special examples of nano-and micro-composite materials, of which the constituent particles and macromolecular structures are both of organic and inorganic nature [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Enamel has 3 essential enamel proteins to build healthy well mineralized enamel which is secreted from ameloblasts "amelogenin, ameloblastin and enamelin" with the help of two enzymes, MMP20 and kallikrein-4 (Klk4) to form the enamel properly and sequent proteolysis of enamel protein [56]. In the event of alteration in the process of protein removal, enamel and dental defects will emerge like for example, amelogenesis imperfecta (AI), Chalky/Molar Hypomolarization (MH), Dentinogenesis Imperfecta (DI) or fluorosis [57]. Figure 3 depicts the protein content in healthy and diseased tooth.…”
Section: Dental Defectsmentioning
confidence: 99%
“…Biomineralization of tooth enamel or amelogenesis is a biologically programmed sequence of several consecutive stages, including two major functional stages: secretory and maturation. 202 204 During the secretory stage, ameloblasts are mainly responsible for producing enamel matrix proteins and proteinases, which control the shape and arrangement of initially formed enamel crystals. 19 At the maturation stage, the thickness and width of enamel crystals greatly expand, accompanied by a decrease in protein abundance, and eventually form a highly mineralized tissue consisting of ~96 wt.% of mineral and a small amount of residual biomacromolecules and water.…”
Section: Enamel Remineralizationmentioning
confidence: 99%
“…At the maturation stage of enamel, the cleavage and degradation of the proteinaceous matrix via proteolytic processes are crucial for the formation of enamel with a high degree of mineralization. 202 A study by Moradian-Oldak et al 216 demonstrated that the occlusion of undegraded amelogenin inside enamel crystals of mice occurred due to the lack of matrix metalloprotease-20 (MMP-20) during amelogenesis. Due to amelogenin occlusion, the enamel crystals in MMP-20 null mice had uncommon sizes, morphologies, and crystallinities.…”
Section: Enamel Remineralizationmentioning
confidence: 99%